Evaluation of anterior mediastinal solid tumors by CT perfusion: a preliminary study - Selim Bakan; Sedat Giray Kandemirli; Atilla Süleyman Dikici; Ezel Erşen; Onur Yıldırım; Cesur Samancı; Şebnem Batur; Deniz Çebi Olgun; Fatih Kantarcı; Canan Akman (Diagnostic and Interventional Radiology, 2017)

(untitled)
PURPOSE:We aimed to assess the role of computed tomography (CT) perfusion in differentiation of thymoma from thymic hyperplasia, lymphoma, thymic carcinoma, and lung cancer invading anterior mediastinum.METHODS:In this study, 25 patients with an anterior mediastinal lesion underwent CT perfusion imaging from January 2015 to February 2016. Diagnoses included thymoma (n=7), thymic hyperplasia (n=8), lymphoma (n=4), thymic carcinoma (n=3), and invasive lung cancer (n=3). Lymphoma, thymic carcinoma, and lung cancer were grouped as malignant tumors for statistical analysis. Values for blood flow, blood volume, and permeability surface were measured in CT perfusion.RESULTS:Blood flow and blood volume values were higher in thymoma in comparison to thymic hyperplasia; however, the difference was not statistically significant. Blood volume values were significantly higher in thymoma (mean, 11.4 mL/100 mL; range, 5.2–20.2 mL/100 mL) compared with lymphoma (mean, 5.3 mL/100 mL; range, 2.5–7.2 mL/100 mL) (P = 0.023). Blood flow and blood volume values were significantly higher in thymoma compared with non-thymoma malignant tumors (P = 0.025).CONCLUSION:CT perfusion is helpful in differentiating thymoma from non-thymoma malignancies including lymphoma, thymic carcinoma, and invasive lung cancer involving the anterior mediastinum.